Tujuan Pemidanaan Rehabiltasi bagi Pelaku Ganja Medis - Rikwan Yuda Pratama (UNES Law Review, 2024)
Objective of Financing in Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana has included Rehabilitation as part of the financing that can be dropped for offenders. In the case of Fidelis who uses Ganja for medical purposes that are Group I Narcotics to treat his wife who has been diagnosed with Syringomyelia. Fidelis is subject to article 116 (1) of the Narcotics Act and is sentenced to eight months imprisonment, a fine of Rp. 1,000,000,000 subsider, one month imprisonement, regardless of the emergency circumstances experienced by Fidelis. Later in a similar case, Rossy was sentenced to 10 months in prison for allegedly violating article 127, paragraph 1, letter a of the Narcotic Drugs Act for consuming cannabis plants to treat the severe nervous disease he suffered. Rehabilitation, both medically and socially, is expected to be a legal breakthrough that can be applied to medical marijuana perpetrators as a form of punishment (sanctions/acts) aimed at benefiting the perpetrator. In understanding the crime policy, looking at the purposes of mediation with the various existing theories should open up new thoughts for law enforcement in terms of combating crime. Then the purposes of the investigation on the New Covenant must also be taken into consideration by the prosecution, because if the judge is not thorough in digging a problem then the scripture that is in the New covenant is only a rigid writing